2011
DOI: 10.5395/jkacd.2011.36.5.377
|View full text |Cite
|
Sign up to set email alerts
|

Rheological characterization of thermoplasticized injectable gutta percha and resilon

Abstract: Objectives:The purpose of this study was to observe the change in the viscoelastic properties of thermoplasticized injectable root canal filling materials as a function of temperature and to compare the handling characteristics of these materials. Materials and Methods: Three commercial gutta perchas and Resilon (Pentron Clinical Technologies) in a pellet form were heated in the Obtura-II system (Obtura Spartan) at 140℃ and 200℃, and the extrusion temperature of the thermoplasticized materials was measured. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Previous studies have demonstrated that such thermoplastic behaviour is attributed to a transition of crystalline phase of GP polymer to amorphous phase (Deanin 1972, Schilder et al 1974. The phase transition temperatures of GP, trans-polyisoprene, from crystalline b-phase to aphase and further to amorphous phase are reported somewhat differently in studies using different test methods, such as X-ray diffraction (Leeper & Schlesinger 1953), thermo-mechanical methods (Schilder et al 1974, Tsukada et al 2004, Chang et al 2011 or calorimetric method (Marciano & Michailesco 1989, Combe et al 2001, Maniglia-Ferreira et al 2008, Ferrante et al 2011. The results of present study showed that thermoplastic GPs have already started to soften before 40°C as shown in Fig.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…Previous studies have demonstrated that such thermoplastic behaviour is attributed to a transition of crystalline phase of GP polymer to amorphous phase (Deanin 1972, Schilder et al 1974. The phase transition temperatures of GP, trans-polyisoprene, from crystalline b-phase to aphase and further to amorphous phase are reported somewhat differently in studies using different test methods, such as X-ray diffraction (Leeper & Schlesinger 1953), thermo-mechanical methods (Schilder et al 1974, Tsukada et al 2004, Chang et al 2011 or calorimetric method (Marciano & Michailesco 1989, Combe et al 2001, Maniglia-Ferreira et al 2008, Ferrante et al 2011. The results of present study showed that thermoplastic GPs have already started to soften before 40°C as shown in Fig.…”
Section: Discussionmentioning
confidence: 49%
“…, Chang et al . ) or calorimetric method (Marciano & Michailesco , Kolokuris et al . , Combe et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A variety of materials and techniques have been developed to improve the sealing quality and reinforcing effect of root canal obturation (30). With the CLC technique, it has been shown that the apical seal is best produced when the spreader can be placed close to the working length (31). The spreader's shape and its depth of penetration are considered to be important factors in producing a more homogenous root canal filling (32).…”
Section: Discussionmentioning
confidence: 99%